The Impact of Interpersonal Style on Ruptures and Repairs in the Therapeutic Alliance Between Offenders and Therapists in Sex Offender Treatment. (October 2017) - Watson, Rachael; Thomas, Stuart; Daffern, Michael
The therapeutic relationship is a critical component of psychological treatment. Strain can occur in the relationship, particularly when working with offenders, and more specifically, those offenders with interpersonal difficulties; strain can lead to a rupture, which may affect treatment participation and performance. This study examined ruptures in the therapeutic relationship in sexual offenders participating in offense-focused group treatment. Fifty-four sex offenders rated the therapeutic alliance at the commencement and completion of treatment; at the completion of treatment, they also reported on the occurrence of ruptures and whether they believed these ruptures were repaired. Ruptures were separated by type, according to severity—Each relationship was therefore characterized as experiencing no rupture, a minor rupture, or a major rupture. Offender characteristics including interpersonal style (IPS) and psychopathy were assessed at the commencement of treatment; their relationship with ruptures was examined. Results revealed that more than half of the offenders (approximately 55%) experienced a rupture in the therapeutic alliance, with one in four of these ruptures remaining unresolved. Offenders who did not report a rupture rated the therapeutic alliance significantly higher at the end of treatment compared with those offenders who reported a rupture that was not repaired. Offenders who reported a major rupture in the therapeutic relationship were higher in interpersonal hostility and hostile-dominance. No interpersonal or offense-specific factors affected the likelihood of a rupture repair.